Augustan culture an interpretive introduction - Galinsky, Karl 1942-2024 (Princeton University Press, 1996)
Galinsky draws on source material ranging from coins and inscriptions to the major works of poetry and art, and challenges the schematic concepts and dichotomies that have commonly been applied to Augustan culture. He demonstrates that this culture was neither monolithic nor the mere result of one man's will. Instead it was a nuanced process of evolution and experimentation. Augustan culture had many contributors, as Galinsky demonstrates, and their dynamic interactions resulted in a high point of creativity and complexity that explains the transcendence of the Augustan age. Far from being static, its sophisticated literary and artistic monuments call for the active response and involvement of the reader and viewer even today